Identification of two near-identical novel HIV-1 unique recombinant forms (CRF01_AE/B) among men who have sex with men in baoding, hebei, China - Zhang, Binbin; Chen, Sisi; Meng, Juan; Su, Miaomiao; Fan, Weiguang; An, Weina; Lu, Xinli (Frontiers in Genetics, 2023)
Men who have sex with men (MSM) are the most frequent infection route of the human immunodeficiency virus (HIV) in Baoding, China, creating chances for the occurrence of unique recombinant forms (URFs) of the virus, i.e., recombination of different subtypes caused by co-circulation of multiple subtypes. In this report, two near-identical URFs (BDD002A and BDD069A) isolated from MSM in Baoding were identified. Phylogenetic tree analysis based on nearly full-length genomes (NFLGs) revealed that the two URFs formed a distinct monophyletic cluster with a bootstrap value of 100%. Recombinant breakpoints analysis identified that the NFLGs of BDD002A and BDD069A were both composed of CRF01_AE and subtype B, with six subtype B mosaic segments inserted into the CRF01_AE backbone. The CRF01_AE segments of the URFs clustered closely with the CRF01_AE reference sequences, and the B subregions clustered with the B reference sequences. The recombinant breakpoints of the two URFs were almost identical. These results suggest that effective interventions are urgently needed to prevent the formation of complex HIV-1 recombinant forms in Baoding, China.